Parental empowerment strategies on stress levels in pediatric intensive care settings: A Literature Review - Aulia Gawara; Yufitriana Amir; Agrina Agrina (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Having a child admitted to the intensive care unit (ICU) is an extremely distressing experience for parents. This heightened stress can negatively affect their mental health and their capacity to support their child's recovery process. To address this, a range of interventions aimed at empowering parents has been developed. Nonetheless, a comprehensive evaluation of the effectiveness of these interventions in alleviating parental stress is still lacking. Purpose: To evaluate different parent empowerment strategies used in pediatric critical care settings and examine their effects on reducing stress among parents. Method: A systematic review was carried out, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for selecting relevant studies. The review began with formulating clinical questions and defining PICOS criteria—P (Population): parents of children in the pediatric intensive care unit (PICU); I (Intervention): empowerment strategies for parents; C (Comparison): routine care without empowerment or parent groups not receiving targeted interventions; O (Outcome): parental stress levels during ICU hospitalization; S (Study design): randomized controlled trials. The literature search used specific keywords, including: “Parent Empowerment,” “Family Centered Care,” “Pediatric Intensive Care,” “PICU,” “NICU,” and “Parental Stress.” Results: Interventions involving educational support, parental empowerment, and family engagement contribute to better mental health outcomes for parents, particularly enhancing their ability to care for critically ill or premature infants in the NICU. Conclusion: Empowerment strategies in pediatric intensive care settings are effective in lowering stress among parents. This review underscores the importance of educational initiatives, family involvement, supportive empowerment techniques, and digital tools such as telenursing in promoting parents' psychological resilience and participation in infant care.